Changes in the use and uptake of a national out-of-hours telephone triage service by younger and older patients seeking non-urgent unplanned care surrounding the COVID-19 pandemic in Flanders (Belgium). Issue 2 (4th March 2023) - Islam, Farah; Milisen, Koen; Gellens, Marc; Enckels, Joël; Kocot, Ewa; Sowada, Christoph; Sabbe, Marc
ABSTRACT: Background: This study seeks to examine if and how the COVID-19 pandemic has prompted changes in the use and uptake of a national out-of-hours (OOH) telephone triage service by younger and older patients seeking non-urgent unplanned care in Flanders (Belgium). Methods: A descriptive study was conducted using registry data obtained from the 1733 OOH telephone triage service in a Flemish region of Belgium. All calls received between 1 January 2019 and 31 December 2020 were analyzed. Results: A significant association was found between patient age and period of call (χ 2 = 594.54, p < .001). Calls made to the 1733 OOH telephone triage service were significantly less likely to be dispatched to a higher level of urgency by operators compared to calls made before the COVID-19 period (OR = 0.80, 95% CI [0.74–0.85]). While calls concerning older adults were significantly more likely to be dispatched to a higher level of urgency by operators compared to younger adults (regardless of period of call) (65 to 74 yrs: OR = 5.75, 95% CI [4.86–6.80]; 75 to 84 yrs: OR = 15.21, 95% CI [13.18–17.56]; ≥ 85 yrs: OR = 28.77, 95% CI [25.01–33.09]), only 6.7% of all COVID-19 related calls involved older adults over 65 years of age. Conclusion: Findings showed that there was a general decline in the number of calls dispatched to a higher level of urgency by operators during the COVID-19 period but that there were differences in the use and uptake of these services by younger and older age segments.